Community-supported slum-upgrading: Innovations from Kibera, Nairobi, Kenya. (February 2017) - Meredith, Thomas; MacDonald, Melanie
Abstract: Slum upgrading is accepted as a priority for sustainable development. While there are clear challenges to upgrading, local support and community engagement are seen as essential to success. Typical "top-down" approaches led by institutions with power and resources may fail to generate local engagement. Conversely, initiatives led by non-governmental organizations (NGOs), community-based organizations (CBOs) or other self-help groups may garner good community support but may lack institutional and material resources to meet objectives. A hybrid approach that engages the community while mobilizing the resources of governments and large agencies can overcome some of these limitations, but it is not without complications. We examine the process and impact of a slum upgrading pilot project in Kibera, Nairobi, Kenya, that operationalized this hybrid approach by adopting an adaptive management model to promote community engagement. The project was part of the Government of Kenya's Kenya Slum Upgrading Program and involved the Kibera Water and Sanitation Project led by UN-Habitat's Urban Basic Services Branch. The project showed significant early success in building community engagement, but it also encountered significant challenges. We assess the project's success in building community engagement by (a) analyzing documents that reflected the institutional discourse related to the project, (b) examining the record of the implementation of the project, and (c) conducting field surveys and interviews to assess community perception of the project. Survey results show that critical infrastructure in the community has improved over the course of the project and expectations for continued improvement in the future have developed. The study concludes that using an adaptive management approach and strongly promoting community involvement should be the aim of institutions delivering slum-upgrading projects and that this can result in effective, successful development outcomes. While the approach does present significant risks of creating unrealistic expectations, the benefits to project management are clear. Highlights: Slum upgrading requires synergies between community and institutional actors. Kenya Slum Upgrading Program provided a strong rhetorical framework for synergy. Adaptive management in a program to provide urban basic services proved effective. Community satisfaction was high and expectation for future outcomes very positive. Resulting expectations may prove volatile if community expectations are not met.